Visualisasi Open Governance Data untuk Analisis Keterkaitan Human Capital Index dan e-Government Development Index - Cut Alna Fadhilla (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2026)
Open Governance Data is an approach that supports the open, integrated, and transparent management of data to generate valuable information for data-driven decision-making. The utilization of open data has become increasingly important in supporting digital government transformation and achieving sustainable development goals. This study aims to analyze the relationship between the Human Capital Index (HCI) and the E-Government Development Index (EGDI) using an Open Governance Data approach to support sustainable development policymaking. The research data were obtained from international open data sources, including the United Nations E-Government Survey 2020, 2022, and 2024, as well as Human Capital Index data from the World Bank. The study employed a quantitative approach consisting of data collection, data integration, data preprocessing, descriptive analysis, comparative analysis, and data visualization. The results indicate that countries with higher Human Capital Index scores tend to achieve better E-Government Development Index performance. These findings suggest that human capital quality plays a significant role in supporting the success of digital government transformation. Furthermore, the implementation of Open Governance Data enables the integration of multiple open data sources to produce comprehensive information for policy planning, monitoring, and evaluation. This study proposes an Open Governance Data-based analytical model that can support more effective, transparent, and evidence-based sustainable development decision-making